Estimation of the Detection Limit of Tritium Storage Bed - Bulubasa, G.; Stefanescu, I.; Bidica, N.; Deaconu, Mariea; Bucur, C.; Vasut, Felicia (Asian Journal of Chemistry, 2010)
Large amounts of tritium can be stored, in a safely manner, as metal tritides. An experimental model of a tritium storage bed with integrated system for in situ tritium inventory accountancy was designed and manufactured at ICIT Rm. Valcea. The calibration curve and the detection limit for this experimental model of tritium storage bed were determined experimentally. An important issue is to know the exact amount of tritium stored inside the bed. The detection limit was determined by calculating the mean blank signal (zero heat injected in the electrical resistance) and the standard deviation of the blank signal and then treating the resulting data statistically.